La familia Mendoza, ejemplo de patronazgo femenino en la edad moderna - Juana Hidalgo Ogáyar (Nuevo mundo - Mundos Nuevos, 2008)
The female patronage in Spain is studied through ten women belonging to the Mendoza family who lived during the 16th century and the beginning of the 17th century. Eight of these women had a connection with Alcalá de Henares where they performed all their patronage. Besides, it is proved that their family circumstances were decisive to develop different patronages.